2021
DOI: 10.1021/acs.nanolett.1c01133
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adjuvant Effect by Manipulating the Bionano Interface of Liposome-Based Nanovaccines

Abstract: Nanovaccines are of increasing scrutiny due to their plasticity in size, composition, and surface properties to enhance antigenicity. However, inevitable absorption of plasma proteins affects the in vivo fate of nanovaccines by reshaping biological identity. Herein IgM was validated as a self-adjuvant by regulating antigen-presenting cells recognition of liposome-based nanovaccines. DCDX-modified liposomes with loading of ovalbumin (DCDX-sLip/OVA) heavily absorbed IgM via electrostatic interaction, demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The in vivo process of targeted delivery systems is extremely complicated. , The formation of protein corona, which alters the synthetic identity to biological one and severely affects in vivo performance of nanocarriers (e.g., targeting ability, pharmacokinetics, immunogenicity), has received increasing attention. We recently found that natural IgM in blood avidly absorbed on the surface of FA-functionalized liposomes (FA-sLip) to hinder receptor recognition, rapidly activating complement and accelerating blood clearance of liposomes. Evading IgM absorption-mediated complement activation and downstream cascade is a key point for improving the in vivo performance and achieving FA-enabled targeting.…”
Section: Fa-discs Restrict Distribution Of the Bound Igm On The Highl...mentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo process of targeted delivery systems is extremely complicated. , The formation of protein corona, which alters the synthetic identity to biological one and severely affects in vivo performance of nanocarriers (e.g., targeting ability, pharmacokinetics, immunogenicity), has received increasing attention. We recently found that natural IgM in blood avidly absorbed on the surface of FA-functionalized liposomes (FA-sLip) to hinder receptor recognition, rapidly activating complement and accelerating blood clearance of liposomes. Evading IgM absorption-mediated complement activation and downstream cascade is a key point for improving the in vivo performance and achieving FA-enabled targeting.…”
Section: Fa-discs Restrict Distribution Of the Bound Igm On The Highl...mentioning
confidence: 99%
“…However, nearly all FA-enabled targeted therapeutics in clinical trials ended in failure. The delivery process of nanocarriers in vivo is complicated, and the formation of protein coronas is now attracting increasing attention. Natural IgM is a highly effective opsonin to trigger classic complement activation after absorption on the particle surface, severely affecting the in vivo performance of nanocarriers. , We recently found that natural IgM in blood avidly absorbed on the surface of FA-functionalized liposomes to impair the delivery efficiency. Evading IgM absorption-mediated complement activation is a key point to improve the in vivo performance.…”
Section: Fa-discs Restrict Distribution Of the Bound Igm On The Highl...mentioning
confidence: 99%
“…IgM (after spontaneous absorption on the nanosurface) serve as self-adjuvant by regulating antigen-presenting cell recognition and complement activation [106] Carriers consisting of non-encoding RNA complexed with protamine (a cationic protein activating TLR7) naked 1-methylpseudouridine modified mRNA to small-molecule TLR2 and TLR7 agonists [107] Lipid-PLGA nanoparticles Hyaluronic acid (HA)-decorated cationic lipid-poly(lactide-co-glycolide) acid (PLGA) hybrid nanoparticles (HA-DOTAP-PLGA NPs) [108] Nanoemulsions A self-assembled biocompatible cationic-covered with hyper-branched poly(ethyleneimine) nanoemulsion has superior adjuvant activity than the non-cationic and traditional adjuvants in vivo.…”
Section: Nanovaccine Complex Compound/adjuvant Properties Referencesmentioning
confidence: 99%
“…Liposome has been widely used for drug delivery in the medical field, for its good biocompatibility, low toxicity, and high loading capacity. The introduction of polyethylene glycol (PEG) to liposome extended circulation in blood. PEG forms a brush-like protective layer on the surface to sterically stabilize liposome and to reduce recognition by opsonins and then is subsequent cleared by the mononuclear phagocyte system (MPS). , PEGylated liposomes have been developed such as Doxil, an early approved anticancer nanomedicine by FDA in 1995, with doxorubicin (DOX) encapsulated in the aqueous core of a liposome and used in advanced ovarian cancer, multiple bone marrow cancer, and Kaposi’s sarcoma complicated by HIV .…”
Section: Introductionmentioning
confidence: 99%